The Problem of Transforming Values into Prices - Hall, Luis J. (San José: Editorial Universidad de Costa Rica, 2011)
The object of this paper is to describe and analyze in a formal and integrated way the alternative solutions proposed to the problem of transforming labor values into prices. Considering that the literature on this topic is sometimes diffused, this paper presents in a unified way the solutions advanced following a mathematical treatment and presentation. Special emphasis is paid to a new normalization procedure that emphasize on the role of the labor theory value as a theory of value formation rather than price. In this tradition, prices will tend to assign or distribute value across society. As opposed to this approach, the paper also contrasts and analyzes the classical approach that focuses on the simultaneous determination of price and value. The paper is then a search for a unified treatment of the topic.